Food Microstructures : Microscopy, Measurement And Modelling. - Morris, V. J. (Elsevier Science, 2013)
The development of high-quality foods with desirable properties for both consumers and the food industry requires a comprehensive understanding of food systems and the control and rational design of food microstructures. Food microstructures reviews best practice and new developments in the determination of food microstructure. After a general introduction, chapters in part one review the principles and applications of various spectroscopy, tomography and microscopy techniques for revealing food microstructure, including nuclear magnetic resonance (NMR) methods, environmental scanning.
7.5 Exemplars of acoustic microscopy and applications to food structure.
Keywords: Food -- Composition.; Food -- Analysis.; Microstructure.; elektronické knihy; electronic books